Self-perception of teaching performance in distance education: evidence from the course Matemática Nivelatoria at UNED (Revista Electrónica Calidad en la Educación Superior, 2025)
This descriptive-evaluative study employed an expert-validated mixed self-evaluation questionnaire sent to seven UNED tutors in the bridging Mathematics course; only three responded. Findings reveal uneven mastery of the institutional model, reliance on extrinsic motivators, fragmented self-regulation scaffolds and mainly corrective, delayed feedback—a combination linked to dropout and irregular achievement. The paper recommends a practice-oriented development programme, integrated self-regulation scaffolding, a continuous multimodal feedback system and strategies that cultivate intrinsic motivation, all to be monitored longitudinally to assess impact.
Keywords: distance education; teacher self-evaluation; motivation; self-regulated learning; feedback